Baseline sensitivity of Corynespora cassiicola to metconazole and efficacy of this fungicide. (April 2020) - Zhu, Jiamei; Zhang, Lingyan; Li, Tongtong; Ma, Dicheng; Gao, Yangyang; Mu, Wei; Liu, Feng
Abstract: Triazole fungicides with broad spectra constitute the standard strategy for the management of fungal diseases of cucumber. In this study, the in vitro activities of metconazole were tested based on mycelial growth using 121 Corynespora cassiicola isolates. The distribution of EC50 values of metconazole for 121 isolates was a unimodal curve with a mean of 0.78 ± 0.41 μg mL −1 . Cross-sensitivity data indicated that sensitivity to metconazole did not correlate with sensitivity to difenoconazole, tebuconazole, myclobutanil or hexaconazole ( P  > 0.05). The relative treatment effect values shown by in vivo assays with detached cucumber leaves and potted seedlings indicated that the protective and curative effects of metconazole were higher than those of difenoconazole. Field data suggested that the application of metconazole at 150 g a.i. ha −1 markedly reduced the disease severity and disease incidence of Corynespora leaf spot compared with the effects obtained with difenoconazole treatment, with relative treatment effects of 0.24 and 0.17 for 2017 and 2018, respectively. These findings demonstrate that metconazole could play a vital role in the integrated management of cucumber Corynespora leaf spot. Highlights: Baseline sensitivity of C. cassiicola to metconazole was established. There was no cross-sensitivity relationship between metconazole and other DMIs. Metconazole exhibited excellent preventive and curative activities in vivo. Metconazole reduced disease severity of Corynespora leaf spot markedly in field.